2006
DOI: 10.1073/pnas.0606758103
|View full text |Cite
|
Sign up to set email alerts
|

When motion appears stopped: Stereo motion standstill

Abstract: Motion standstill is different from the usual perceptual experiences associated with objects in motion. In motion standstill, a pattern that is moving quite rapidly is perceived as being motionless, and yet its details are not blurred but clearly visible. We revisited motion standstill in dynamic random-dot stereograms similar to those first used by Julesz and Payne [Julesz B, Payne R (1968) Vision Res 8:433-444]. Three improvements were made to their paradigm to avoid possible confounds: The temporal frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
0
6
1
Order By: Relevance
“…If such training is done adequately, assessments [2,46] show that improvements may occur in nine tested abilities of students and stamina of the visual system. Positive results also appeared for toss-to-wall [46], baseball [2,13,47,48], basketball [49,50], cricket, football [9,51,52], fencing, frisbee [9], hockey [15,53], rugby [54], softball [55,56], tennis, table tennis [57], volleyball [49], and water-polo [49]. Outside of sports, improvements are known for motion sickness [58], older adults [59], and visually impaired youth [60].…”
Section: Methodsmentioning
confidence: 99%
“…If such training is done adequately, assessments [2,46] show that improvements may occur in nine tested abilities of students and stamina of the visual system. Positive results also appeared for toss-to-wall [46], baseball [2,13,47,48], basketball [49,50], cricket, football [9,51,52], fencing, frisbee [9], hockey [15,53], rugby [54], softball [55,56], tennis, table tennis [57], volleyball [49], and water-polo [49]. Outside of sports, improvements are known for motion sickness [58], older adults [59], and visually impaired youth [60].…”
Section: Methodsmentioning
confidence: 99%
“…Observers performed better at slower presentation rates, which is in agreement with previous findings for third-order motion stimuli (Lu & Sperling, 1995), and consistent with the fact that stereo-motion perception declines at higher temporal frequencies. Alternately, the possibility of a decline in stereo-shape extraction at faster presentation rates (Foley & Tyler, 1976) cannot be ruled out as a cause, although Tseng et al (2006) showed that observers are sometimes unable to discriminate motion direction of stereo-defined gratings, even when they clearly perceive the grating. Performance declined for both grating and motion detection at higher temporal frequencies.…”
Section: Resultsmentioning
confidence: 99%
“…It is theoretically possible that the different static and flicker MAE directions are due to the different contributions of the first-order and second-order motion mechanisms. Luminance gratings can stimulate the second-order, as well as the first-order and third-order motion systems 65 70 . If we assume that second-order motion mechanism is responsible to flicker MAE, we can still explain the results with replacing the fast motion mechanism by the second-order motion system.…”
Section: Discussionmentioning
confidence: 99%